TOOLKIT FOR THE ADAPTATION OF THE ENTERPRISE TO THE COMPETITIVE ENVIRONMENT: ASPECTS OF INFORMATION TECHNOLOGY SECURITY - NAKONЕCHNA Natalіya; HRADYUK Natalііa (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The study reveals issues of managing the viability of economic entities. It is shown that one of the vectors of the policy of ensuring the viability of the enterprise is its adaptation to the competitive environment. In turn, such adaptation depends to a large extent on the timely involvement and effective use of information technology tools for adapting the enterprise to the competitive environment. The purpose of the research is to substantiate the toolkit of the enterprise’s adaptation to the competitive environment with the use of information technology support. The directions of such adaptation are determined. This is the formation and increase of competitive advantages, increasing competitive potential, strengthening competitive positions, increasing competitiveness. In difficult economic conditions caused by a full-scale war, the issue of ensuring the viability of Ukrainian enterprises comes to the fore. At the same time, enterprises should not only maintain their own internal financial and economic stability, but also adapt to the changing competitive environment. For such purposes, one should activate its own information and technological support. It is important to conduct the corresponding policy in the following directions: formation and increase of competitive advantages, increase of competitive potential, strengthening of competitive positions, increase of competitiveness, when the digital transformation of business processes serves as the tools of the first of them; introduction of automation and robotization technologies of business operations; development of an electronic commerce system; increasing the share of products with digital technologies; the second is the creation of an information system for making strategic management decisions; activation of participation in innovative and technological projects of inter-branch and inter-regional cooperation; diversification of forms and means of innovative and technological modernization of business; the third – activation of innovative and technological activity; increasing the level of information security and data protection; implementation of informational and analytical observations and implementation of marketing and promotional programs; fourth – modernization of the computer and information base; introduction of information and communication technologies and creation of a network of interactive platforms (centers); implementation of information digital entrepreneurship projects.